Correlation of dental anxiety with oral health status and treatment needs among 12-year old indian school going children: Dental Anxiety and Oral Health - Chakradhar, Kuracha; Dolar, Doshi; Kulkarni, Suhas; Srikanth Reddy, Bandari; Padma Reddy, Madupu; Srilatha, Adepu (Acta Biomedica Atenei Parmensis, 2020)
BACKGROUND and AIM: Dental anxiety is primarily associated with learning negative behaviour which may be attributed to the aggressive condition process during childhood and adolescence and is considered to be the main reason for avoiding dental care. Hence the present study aimed to assess the correlation of Dental Anxiety with Oral Health Status and Treatment Needs.METHODS: Cross sectional study was carried out among 12-year old school going children of Hyderabad City, India. Dental anxiety was assessed using the Modified Child Dental Anxiety Scale (MCDAS). Oral Health Status and Treatment Needs were assessed using Gingival Index and Dentition status and treatment needs based on Basic Oral Health Survey. Multi-group analysis was done using Analysis of Variance. p